2005
DOI: 10.1073/pnas.0409766102
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine supersensitivity correlates with D2Highstates, implying many paths to psychosis

Abstract: Dopamine supersensitivity occurs in schizophrenia and other psychoses, and after hippocampal lesions, antipsychotics, ethanol, amphetamine, phencyclidine, gene knockouts of Dbh (dopamine ␤-hydroxylase), Drd4 receptors, Gprk6 (G protein-coupled receptor kinase 6), Comt (catechol-O-methyltransferase), or Th ؊/؊ , Dbh Th/؉ (tyrosine hydroxylase), and in rats born by Cesarean-section. The functional state of D2, or the high-affinity state for dopamine (D2 High ), was measured in these supersensitive animal brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
228
2
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 317 publications
(253 citation statements)
references
References 31 publications
19
228
2
4
Order By: Relevance
“…To explain the underlying mechanisms of this paradoxical hypersensitivity to psychostimulants on the part of Dbh À/À mice, we examined DA transmission by microdialysis and radioligand binding. We found that Dbh À/À mice have a reduction in basal extracellular DA in the NAc and CP, whereas amphetamine-induced DA release is abolished in the NAc and attenuated in the CP and PFC (Schank et al, 2006;Seeman et al, 2005). It is important to note that the 'ectopic' DA produced in 'noradrenergic' neurons in Dbh À/À mice is not the cause of the hypersensitivity; although Dbh À/À mice indeed produce more DA in brain tissue than normal mice (Thomas et al, 1998; Bourdelat-Parks et al, 2005), overall DA release is hampered.…”
Section: Paradoxical Hyperdopaminergic State Following Chronic Ne Depmentioning
confidence: 75%
See 1 more Smart Citation
“…To explain the underlying mechanisms of this paradoxical hypersensitivity to psychostimulants on the part of Dbh À/À mice, we examined DA transmission by microdialysis and radioligand binding. We found that Dbh À/À mice have a reduction in basal extracellular DA in the NAc and CP, whereas amphetamine-induced DA release is abolished in the NAc and attenuated in the CP and PFC (Schank et al, 2006;Seeman et al, 2005). It is important to note that the 'ectopic' DA produced in 'noradrenergic' neurons in Dbh À/À mice is not the cause of the hypersensitivity; although Dbh À/À mice indeed produce more DA in brain tissue than normal mice (Thomas et al, 1998; Bourdelat-Parks et al, 2005), overall DA release is hampered.…”
Section: Paradoxical Hyperdopaminergic State Following Chronic Ne Depmentioning
confidence: 75%
“…It has been well established that the DA system compensates for a loss of dopaminergic tone by upregulating DA receptor signaling capacity, and that is exactly what happens in Dbh À/À mice. Using radioligand binding in the presence and absence of guanine nucleotide, which can discriminate between lowand high-affinity state DA receptors, we found that the density of high-affinity state DA receptors is increased three to to six-fold in the NAc and CP of Dbh À/À mice (Seeman et al, 2005;Schank et al, 2006). Furthermore, Dbh À/À mice are behaviorally hypersensitive to quinpirole, a direct D2 agonist (Weinshenker et al, 2002a).…”
Section: Paradoxical Hyperdopaminergic State Following Chronic Ne Depmentioning
confidence: 96%
“…This suggests a hypodopaminergic state rather than a sensitized state (Volkow et al 2004 (Seeman et al 2005). Most important for the discussion here, cocaine self-administration experience ) and sensitization to amphetamine (Seeman et al 2002(Seeman et al , 2007 have also been reported to produce a persistent increase in the number of striatal D high 2 receptors, with no change in total D 2 binding (and therefore presumably a proportionate decrease in D low 2 receptors).…”
Section: Does Sensitization Occur In Humans?mentioning
confidence: 87%
“…The ligands used in the human and non-human primate imaging studies do not discriminate between the low-and high-affinity states of the D2 receptor and would be, therefore, insensitive to changes in the number of D2 High receptors (Seeman et al, 2003;. Furthermore, there are many examples where an increase in D2 High receptors has been associated with dopamine supersensitivity, even when there was no change or even a decrease in total D2 receptors (Seeman et al, 2005). It is also worth mentioning that the human and non-human primate studies were performed in vivo and thus the apparent decrease in binding could be due to an increase in endogenous dopamine, which would interfere with ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…The transmitter dopamine binds primarily to the high-affinity state of the D2 receptor (D2 High ), making this the most functionally relevant state (Seeman, et al, 2005). Furthermore, many different treatments that produce a functional supersensitivity to dopamine (including repeated amphetamine administration) produce a large increase in the number of D2 High receptors in the dorsal striatum, even if they produce no change or even a decrease in the total number of D2 receptors (Seeman, et al, 2004, Seeman, et al, 2005. Unfortunately, the ligands used in the human imaging and non-human primate studies do not discriminate between the low-and high-affinity states of the D2 receptor and are, therefore, insensitive to changes in the number of D2 High receptors.…”
Section: Introductionmentioning
confidence: 99%